Ventana de nacimiento del pollito COBB-500 y su efecto en la absorción del saco vitelino - Verduga Buste, Juan Carlos (2022)
The effect of the hatching window of the COBB 500 chick on yolk sac absorption was evaluated, a study was proposed using a completely randomized design and Kruskal-Wallis test conforming the treatments: T1 chicks hatched up to 492 hours, T2 hatched up to 498 hours and T3 born up to 504 hours, with random samples of 22 repetitions. The variables considered on days 0, 3 and 7 were chick weight and yolk sac weight, on days 3 and 7 the percentage of yolk sac absorption and weight gain were evaluated. The results show a highly significant difference (p<0.01) for the weight of the chick at birth in T1 with 43.14 g, there was no significant difference (p>0.05) in the weight of the yolk sac at birth, the percentage of absorption of the yolk sac showed a highly significant difference. significant (p<0.01) on the third day with a better result in T3 (91.88%), while on the seventh day there was a highly significant difference (p<0.01), the weight gain presented a highly significant difference (p<0.01) at third day in T3 with 50.32 g, however it does not show significant difference (p>0.05) on the seventh day with 144.75g, for the weight of chicks per week no significant difference was obtained (p>0.05), with better behavior in T3 with 186.32 g. It is concluded that the hatching window influences the weight of the chicks at birth, the absorption of the yolk sac and the weight gain until the first week of life with better performance of the animals incubated for 504 hours.